Sobre Vargaslugo, Elisa, et al., Juan Correa. Su vida y su obra, tomo I, Pedro Ángeles Jiménez y Cecilia Gutiérrez Arriola (coordinadores), México, Universidad Nacional Autónoma de México, Instituto de Investigaciones Estéticas, 2017, 341 pp. (Tzintzun, Revista de Estudios Históricos, 2021)
-